MANAJEMEN PENGELOLAAN KELAS UNTUK MENUMBUHKAN RASA PERCAYA DIRI SISWA SEKOLAH DASAR - Widyaningrum, Atik; Hasanah, Enung (STKIP Pesisir Selatan, 2021)
Classroom management by the teacher is one of the external factors that greatly influences the level of success of a student's learning. Creative and innovative classroom management has the opportunity to spark and grow students' self-confidence. Therefore, there is a close relationship between classroom management and students' self-confidence. This study aims to provide knowledge and understanding to teachers in increasing creativity and innovation in classroom management, so that they can grow and form students' self-confidence, especially elementary school students who are the golden age to shape children's personalities. Seeing how important it is to have a great sense of self-confidence to be able to appear in public without being too nervous. It needs to be trained and familiarized from an early age, one of which is through classroom management by teachers. This study uses a descriptive qualitative method, which is a process of data analysis carried out through the literature study stage. The results of the study indicate that the importance of the role of a teacher in managing the classroom is to trigger the growth and development of students' self-confidence. This can be done by a teacher according to the level of creativity and innovation of each teacher. The higher the level of creativity and innovation of a teacher in managing the classroom, the greater the opportunities and progress of students in building their self-confidence.